2011
DOI: 10.1152/ajplung.00092.2011
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of monocyte subset proinflammatory responses within the lung microvasculature by the p38 MAPK/MK2 pathway

Abstract: Margination and activation of monocytes within the pulmonary microcirculation contribute substantially to the development of acute lung injury in mice. The enhanced LPS-induced TNF expression exhibited by Gr-1high compared with Gr-1low monocytes within the lung microvasculature suggests differential roles for these subsets. We investigated the mechanisms responsible for such heterogeneity of lung-marginated monocyte proinflammatory response using a combined in vitro and in vivo approach. The monocyte subset in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 61 publications
(91 reference statements)
2
34
0
1
Order By: Relevance
“…Twenty-four hours post treatment, cortical windows were created and time-lapse videos were captured at depths up to approximately 200 microns. Leukocytes (monocytes, neutrophils) were labeled using fluorescently conjugated antibody directed against granulocyte antigen 1 (Gr1; aka Ly-6C/G), as murine monocytes expressing high levels of Gr1 have been shown to be representative of the “inflammatory” monocyte population that corresponds to the CD16 high monocyte subset within humans [48][50], and the Gr1 antigen is also representative of a widely used panel of markers for activated monocytes in mice [51][53]. These mice were also exposed to Texas Red Dextran for the illumination of vessels.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-four hours post treatment, cortical windows were created and time-lapse videos were captured at depths up to approximately 200 microns. Leukocytes (monocytes, neutrophils) were labeled using fluorescently conjugated antibody directed against granulocyte antigen 1 (Gr1; aka Ly-6C/G), as murine monocytes expressing high levels of Gr1 have been shown to be representative of the “inflammatory” monocyte population that corresponds to the CD16 high monocyte subset within humans [48][50], and the Gr1 antigen is also representative of a widely used panel of markers for activated monocytes in mice [51][53]. These mice were also exposed to Texas Red Dextran for the illumination of vessels.…”
Section: Resultsmentioning
confidence: 99%
“…Others have shown that exposure of mice to LPS results in inflammation and increased expression of VEGF in the lung (20). Furthermore, VCAM-1 expression is increased in LPStreated mouse lung EC compared with nontreated cells (28). Thus PEDF deficiency in the lung endothelium may promote the progression of inflammation.…”
Section: Discussionmentioning
confidence: 98%
“…Cell suspension and whole blood were incubated with the following fluorophore-conjugated rat anti-mouse mAbs antibodies used: Ly6C (HK1.4) (BioLegend), Gr1 (RB6-8C5) (BioLegend), NK1. [29]. In lung tissue, Ly6C lo subset monocytes were distinguished from interstitial macrophages by low expression of MHC II (Supplementary Figure S1) [30].…”
Section: Flow Cytometrymentioning
confidence: 99%